THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON SERVICE QUALITY AND EMPLOYEE PERFORMANCE IN THE INVESTMENT OFFICE AND ONE STOP INTEGRATED SERVICE IN MAKASSAR CITY - Muhammad Arif Rahmat; Nurdin Brasit; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This study aims to determine the Effect of leadership sale and work discipline on service Quality and Employee Performance in the Investment Office and One-Stop Integrated service in Makassar city. The approach taken in this study was a quantitative approach with the path analysis method. The population in this study are employees at the Department of Investment and one-stop integrated service or the city of Makassar. Data collection techniques used observation, interviews, and questionnaires while data processing using SPSS (Statistical Product and Service solution) version 23. The results showed that there is a positive and significant influence of leadership style on service quality. There is a negative and insignificant influence of work discipline on service quality, there is a positive and significant influence of leadership style on employee performance, there is a negative and insignificant influence of work discipline on employee performance, there is a negative and significant effect of service quality on employee performance, there ia a positive and significant influence of leadership style on employee performance through quality service. There is a negative and insignificant influence of work discipline on employee performance through service quality.